Microbiome Impact on Amyloidogenesis - Seira Curto, Jofre; Surroca Lopez, Amat; Casals Sanchez, Maria; Tic, Iva; Fernandez Gallegos, Maria Rosario; Sanchez de Groot, Natalia (Frontiers in Molecular Biosciences, 2022)
Our life is closely linked to microorganisms, either through a parasitic or symbiotic relationship. The microbiome contains more than 1000 different bacterial species and outnumbers human genes by 150 times. Worryingly, during the last 10 years, it has been observed a relationship between alterations in microbiota and neurodegeneration. Several publications support the hypothesis that amyloid structures formed by microorganisms may trigger host proteins aggregation. In this review, we collect pieces of evidence supporting that the crosstalk between human and microbiota amyloid proteins could be feasible and, probably, a more common event than expected before. The combination of their out numbers, the long periods of time that stay in our bodies, and the widespread presence of amyloid proteins in the bacteria Domain outline a worrying scenario. However, the identification of the exact microorganisms and the mechanisms through with they can influence human disease also opens the door to developing a new and diverse set of therapeutic strategies.